Efektifitas Penerapan Finger Print dalam Meningkatkan Disiplin dan Kinerja Pegawai di SMK Negeri 2 Sangatta Utara Kabupaten Kutai Timur - Rahayu, Sri (Jurnal Nasional Manajemen Pemasaran dan SDM, 2023)
In the last few years, SMK Negeri 2 North Sangatta, East Kutai, has only implemented a management strategy based on the finger print application in improving the discipline of teachers and staff. The time discipline of teachers at SMK Negeri 2 North Sangatta East Kutai was considered good. Discipline is seen based on the recapitulation of employee absences and elements of discipline. Employee time discipline before applying the finger print shows an average presentation of discipline of 70%. Then after the application of finger print, the level of employee discipline at SMK Negeri 2 North Sangatta saw an increase in the level of discipline with attendance increasing 6.2%, absenteeism decreasing 2.5%, and tardiness decreasing 3.5%. This shows that the application of finger print has a positive impact on the level of employee discipline which will ultimately have an impact on employee performance.